Parliamentary Threshold In Integrative Legal Perspective: Indonesian Case - Sholahuddin Al-Fatih (Faculty of Law, Jambi University, 2020)
The article aims at discussing the application of parliamentary threshold legal norms in an integrative legal perspective. Through historical, conceptual and statutory approaches, this study tries to examine holistically and prescriptively the dynamics of applying parliamentary thresholds in legislative elections. This article makes the thinking of leaders on integrative law a benchmark and an analytical knife. The results of this study demostrates that the application of parliamentary thresholds in elections based on an integrative legal perspective is not appropriate because it has not been able to guarantee the fulfillment of a sense of justice for all Indonesians because integrative law views a legal event as a comprehensive state of pros and cons. This research is expected to help academics and legal practitioners, especially with regard to election law to be able to dig out deeper into integrative law, not only from one or two experts, but from several other experts.